Survival and Causes of Mortality of Relocated and Resident Northern Bobwhites in East Texas - Xiangwen Liu; R. Montague Whiting Jr.; Brad S. Mueller; D. Scott Parsons; Donald R. Dietz (National Quail Symposium Proceedings, 2017)
We estimated survival of 3 groups of northern bobwhites (Colinus virginianus) on a 563-ha intensively managed study area in eastern Texas. During the 3-year study, 155 bobwhites from South Texas and 136 bobwhites from East Texas were captured, radio-marked, and relocated to the study area; 139 bobwhites that were resident on the study area were also captured, radio-marked, and released at the point of capture. There were no differences (P > 0.05) in survival among the 3 groups of bobwhites. However, survival of bobwhites from South Texas were consistently lower than those of the other 2 groups during each year; both bobwhites from East Texas and resident bobwhites survived better than bobwhites relocated from South Texas. Avian predation claimed 57.6% of 243 known-fate birds, mammalian predation and apparent capture stress each caused 9.1 % mortality, while 1.2% of the birds died of snake predation and 14.0% were lost to unidentifiable causes.